Folk Music and Commercialization in Danubian Trances and Boheme - Barbara Rose Lange (Dancecult: Journal of Electronic Dance Music Culture, 2015)
Hungary participates in the Central European narrative of rejuvenation and renewal through EDM, but the commercialization of remixes has disturbed that account. Hungarians debate the meanings of two different CD projects: Deep Forest’s 1995 album Boheme and Károly Cserepes’s 2003 album Danubian Trances: mikroworld–ambient. Hungarian fans praise Danubian Trances as an elegant update of national sensibility. Boheme’s remixes of Hungarian and Romani folksong have earned a very different response, from shock at the cuts that Deep Forest made to folk song recordings to anger about cultural appropriation. Hungarians have reflected that Boheme, like many West European firms, extracted a resource from the country. By contrast, they view their own remixing of folk music from the peoples of the former Austro-Hungarian Empire as having continuity with other genres that elevate folksong. I argue that where commerce encounters a previous practice of elevating music aesthetically and morally, it may further marginalize that practice but it does not change its character.